External radiotherapy of pituitary adenomas - Zierhut, Dietmar; Flentje, Michael; Adolph, Jürgen; Erdmann, Johannes; Raue, Friedhelm; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 1995)
Purpose: To evaluate therapeutic outcome and side effects of radiotherapy in pituitary adenomas as sole or combined treatment. Methods and Materials: Retrospective analysis of 138 patients (74 male, 64 female) irradiated for pituitary adenoma from 1972 to 1991 was performed. Mean age was 49.7 years (15-80 years). Regular follow-up (in the mean 6.53 ± 3.99 years) included radiodiagnostical [computed tomography (CT), magnetic resonance imaging (MRI), x-ray], endocrinological, and ophthalmological examinations. Sevently patients suffered from nonfunctional pituitary adenoma, 50 patients suffered from growth-hormone producing adenomas, 11 had prolactinomas, and 7 patients had adrenocorticotropic hormone (ACTH) producing pituitary adenomas. In 99 patients surgery was followed by radiotherapy in case of suspected remaining tumor (invasive growth of the adenoma, assessment of the surgeon, pathologic CT after surgery, persisting hormonal overproduction). Twenty-three patients were treated for recurrence of disease after surgery and 16 patients received radiation as primary treatment. Total doses from 40-60 Gy (mean: 45.5 Gy) were given with single doses of 2 Gy 4 to five times a week. Results: Tumor control was achieved in 131 patients (94.9%). In seven patients, recurrence of disease was diagnosed in the mean 2.9 years (9-98 months) after radiotherapy and salvaged by surgery. A statistically significant dose-response relationship was found in faver of doses ≥ 45 Gy. Ninety percent of the patients with hormonally active pituitary adenomas had a benefit from radiotherapy in means of complete termination (38%) or at least reduction (52%) of hormonal overproduction. Partial or complete hypopituitarism after radiotherapy developed, depending on hormonal axis, in 12 (prolactin) to 27% (follicle-stimulating hormone FSH) of patients who had not already had hypopituitarism prior to radiation. Two out of 138 patients suffered reduction of visual acuity, which was, in part, related to radiotherapy. Both therapeutic effects and side effects occurred after a latency period of 3 months up to 9 years. Conclusion: We conclude that radiotherapy of pituitary adenomas, using modern treatment planning techniques, is effective and safe. To achieve optimal tumor control, doses of 45-48 Gy (conventionally fractionated) should be applied.